Case Report: Late-Onset Mitochondrial Disease Uncovered by Metformin Use in a Patient With Acute Verbal Auditory Agnosia - Lin, Wei-Hao; Yang, I-Hsiao; Cheng, Hui-En; Lin, Hsiu-Fen (Frontiers in Neurology, 2022)
Introduction: Verbal auditory agnosia is rarely caused by mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes syndrome. Lactate acidosis, the adverse effect of metformin, has proposed links to mitochondrial dysfunction and may trigger clinical features of mitochondrial diseases. Case presentation: A 43-year-old right-handed man presented to our emergency department with acute onset fever and headache accompanied by impaired hearing comprehension. He could communicate well through handwritten notes but could not understand what others were saying. He had been diagnosed as having diabetes mellitus 2 months prior to this event. Vildagliptin 100 mg/day and metformin 1700 mg/day were prescribed for glucose control. Laboratory tests revealed elevated lactate level in serum and cerebrospinal fluid. Brain MRI disclosed bilateral temporal lesions. Acute encephalitis with temporal involved was initially diagnosed and acyclovir was given empirically. However, follow-up MRI after acyclovir treatment revealed a progression of prior lesions. Further mitochondrial genome analysis revealed a mitochondrial DNA point mutation at position 3243 (m.3243A>G) with 25% heteroplasmy, which is compatible to MELAS. His clinical symptoms and serum lactate level were improving after discontinued the metformin use. Conclusions: To our knowledge, this is the first report of a patient having late-onset MELAS syndrome that manifested as acute verbal auditory agnosia, which was identified after the patient began using metformin. Metformin is known to inhibit mitochondrial function and could trigger clinical features of MELAS syndrome. We encourage clinicians to maintain a high level of awareness that diabetes mellitus can be caused by mitochondrial disease and to exercise caution in the prescription of metformin.